Large-scale and high-quality III-nitride membranes through microcavity-assisted crack propagation by engineering tensile-stressed Ni layers - Jung-Hong Min; Kwangjae Lee; Tae-Hoon Chung; Jung-Wook Min; Kuang-Hui Li; Chun Hong Kang; Hoe-Min Kwak; Tae-Hyeon Kim; Youyou Yuan; Kyoung-Kook Kim; Dong-Seon Lee; Tien Khee Ng; et al. (Opto-Electronic Science, 2022)
Epitaxially grown III-nitride alloys are tightly bonded materials with mixed covalent-ionic bonds. This tight bonding presents tremendous challenges in developing III-nitride membranes, even though semiconductor membranes can provide numerous advantages by removing thick, inflexible, and costly substrates. Herein, cavities with various sizes were introduced by overgrowing target layers, such as undoped GaN and green LEDs, on nanoporous templates prepared by electrochemical etching of n-type GaN. The large primary interfacial toughness was effectively reduced according to the design of the cavity density, and the overgrown target layers were then conveniently exfoliated by engineering tensile-stressed Ni layers. The resulting III-nitride membranes maintained high crystal quality even after exfoliation due to the use of GaN-based nanoporous templates with the same lattice constant. The microcavity-assisted crack propagation process developed for the current III-nitride membranes forms a universal process for developing various kinds of large-scale and high-quality semiconductor membranes.